Lipids at the Crossroad of α-Synuclein Function and Dysfunction: Biological and Pathological Implications - Alza, Natalia P.; Iglesias González, Pablo A.; Conde, Melisa A.; Uranga, Romina M.; Salvador, Gabriela A. (Frontiers in Cellular Neuroscience, 2019)
Since its discovery, the study of the biological role of α‑synuclein and its pathological implications has been the subject of increasing interest. The propensity to adopt different conformational states governing its aggregation and fibrillation makes this small 14 kDa cytosolic protein one of the main etiologic factors associated with degenerative disorders known as synucleinopathies. The structure, function and toxicity of α‑synuclein and the possibility of different therapeutic approaches to target the protein have been extensively investigated and reviewed. One intriguing characteristic of α‑synuclein is the different ways in which it interacts with lipids. Though in-depth studies have been carried out in this field, the information they have produced is puzzling and the precise role of lipids in α‑synuclein biology and pathology and vice versa is still largely unknown. Here we provide an overview and discussion of the main findings relating to α‑synuclein/lipid interaction and its involvement in the modulation of lipid metabolism and signaling.